WHAT DO DENTISTS NEED TO KNOW ABOUT CROHN'S DISEASE? - Fernando Gabriel de Araújo Chagas; Anna Thereza Thomé Leão; Sandra Regina Torres (Portal de Periódicos da Marinha do Brasil, 2021)
Crohn's disease is described as a complex inflammatory bowel disease, characterized by transmural lesions and inflammation that can affect the entire gastrointestinal tract. Crohn's disease can present oral manifestations, such as mucosal lesions, changes in salivary flow rates and periodontal involvement. For this review, a literature search was carried out using PubMed, Scielo and Scholar Google platforms, within the time range from 2010 to 2020, using keywords obtained according to the Health Science Descriptor. We found that oral lesions are present in approximately 46.75% of young patients and 22% of elderly patients with Crohn's disease, which can be uncomfortable, persistent and difficult to treat. They are associated with various clinical aspects such as: linear or aphthous ulcers, mucosal nodularities and increased lip volume. These lesions are directly related to the disease, but some lesions may appear indirectly, as a complication of Crohn's disease or as adverse effects of the treatment. Oral manifestations can be the first signs of Crohn's disease, so the recognition of its clinical aspects can contribute to an early diagnosis. Dentists should be able to recognize, diagnose and treat, along with a multidisciplinary team, the oral manifestations of Crohn's disease, promoting improvements in the patient's clinical condition.